2022
DOI: 10.1080/24735132.2022.2060649
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of implementing design research within SME based medical product development: Paxman scalp cooling case study

Abstract: This paper examines a long-term study on patient experience to identify value generated through collaborative medical design research, in developing a scalp cooling device to prevent chemotherapy-induced alopecia (CIA)/ hair-loss. Developing a new medical device is long and complex, requiring a cross-platform multi-disciplinary team. User feedback is essential to ensure continuous development to improve efficacy. Qualitative and quantitative data was gathered from chemotherapy patients using scalp cooling in 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…We collected anthropometric data from cephalic, circumference, and shape profiles to establish how accurate and viable each method was for gathering data against what we currently know from prior Paxman studies. 1,4,5,12 Fifty-five per cent of the pilot study participants reported poor fit in the crown area. This finding was unexpected given that 55 per cent of the participants are of Caucasian background, and they used a Caucasian style cap.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected anthropometric data from cephalic, circumference, and shape profiles to establish how accurate and viable each method was for gathering data against what we currently know from prior Paxman studies. 1,4,5,12 Fifty-five per cent of the pilot study participants reported poor fit in the crown area. This finding was unexpected given that 55 per cent of the participants are of Caucasian background, and they used a Caucasian style cap.…”
Section: Resultsmentioning
confidence: 99%
“…Scalp cooling relies heavily on close fit to the patient's scalp for optimal efficacy. 5 In addition to safety and efficacy, other crucial parameters for the design process are properties attributed to the cap materials-namely, flexibility, tear resistance, ability to hold liquids at pressure, comfort, heat exchange capabilities, and regulatory requirements such as biocompatibility.…”
Section: Case Studymentioning
confidence: 99%
“…From the 175 studies a collection of relevant papers 1,2,3,4,5,6 focused on the human head size data, which had the most impactfil influence on this study, including studies such as SizeChina, Caesar, Gayre's race studies, and some of the research team's published literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers retrieved more than 175 papers, including journal articles, clinical studies, conference studies, and content from master's and PhD theses. From the 175 studies a collection of relevant papers 1,2,3,4,5,6 focused on the human head size data, which had the most impactfil influence on this study, including studies such as SizeChina, Caesar, Gayre's race studies, and some of the research team's published literature.…”
Section: Literature Reviewmentioning
confidence: 99%